2019
DOI: 10.1088/1361-6587/ab471b
|View full text |Cite
|
Sign up to set email alerts
|

Using dynamical mode decomposition to extract the limit cycle dynamics of modulated turbulence in a plasma simulation

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…These LCOs may significantly affect overall plasma performance, so that understanding their underlying physics is important. While the assumption of exponential time dependence in DMD treatments can be mitigated to some extent [17], DMD is not well adapted to LCOs where, as in the present paper, there is a cyclic rise and fall in the intensity of turbulence, of turbulence-driven structures, and of the coupling between them.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…These LCOs may significantly affect overall plasma performance, so that understanding their underlying physics is important. While the assumption of exponential time dependence in DMD treatments can be mitigated to some extent [17], DMD is not well adapted to LCOs where, as in the present paper, there is a cyclic rise and fall in the intensity of turbulence, of turbulence-driven structures, and of the coupling between them.…”
Section: Introductionmentioning
confidence: 83%
“…2 for Fourier space, or Fig. 1 of [17] for real space. The nine spatial structure functions shown in the left panel of Fig.…”
Section: Evaluation Of Energy Transfer By Svdmentioning
confidence: 99%
See 1 more Smart Citation
“…Their work showed that DMD produces spatio-temporal structures that are more physically interpretable than BOD modes and captures the vast majority of the magnetic energy with a simple rank-3 model in both experimental and simulated HIT-SI discharges, suggesting that the device may be amenable to control [59]. Beyond the HIT-SI experiment, DMD has been successfully applied to identify limit-cycle dynamics in 2D turbulent cylindrical plasma simulations [64].…”
Section: Dynamic Mode Decomposition For Plasmasmentioning
confidence: 99%
“…Very recently, POD has been used to characterize axial and azimuthal modes in Hall thruster high-speed video [32] and azimuthal modes in a hollow cathode plume [33]. More sophisticated SVD algorithms exist, most notably DMD (Dynamic Mode Decomposition) [34,35] and have applications in active control, linear dynamics, and plasma physics [36,37,38].…”
Section: Introductionmentioning
confidence: 99%